Multi-layer core-shell structure catalyst as well as preparation method and application thereof

By adding a metal oxide layer on the carbon outer layer of the traditional core-shell catalyst to form a multi-layer core-shell structure catalyst, the problems of weak electron transport capacity and small molecules entering are solved, and higher reactivity and stability are achieved.

CN119793522APending Publication Date: 2025-04-11ZHEJIANG UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411901704.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The thickness of the carbon outer layer of traditional core-shell catalysts results in weak electron transport capabilities and cannot effectively inhibit the entry of small molecules, affecting the catalytic efficiency.

Method used

Add a metal oxide layer containing metal to the carbon outer layer of the existing core-shell catalyst to form a multi-layer core-shell structural catalyst, effectively inhibiting the entry of small molecules and improving electron transport capabilities.

Benefits of technology

The electron transport performance and reactivity of the catalyst are improved, the shielding effect on small molecules is enhanced, and the stability of the catalyst and the selectivity of the target product are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793522A_ABST
    Figure CN119793522A_ABST
Patent Text Reader

Abstract

The multi-layer core-shell structure catalyst comprises a supported metal catalyst, wherein the supported metal catalyst comprises a carrier and an active metal combined with the carrier; wherein the carrier is one of a molecular sieve, a carbon material, a metal oxide, MOF, COF and a composite carrier; the mass of the active metal is 0.1 wt%-15 wt% of the total mass of the supported metal catalyst; the carrier is wrapped with a carbon material, and the carbon material is wrapped with a metal oxide layer; a metal-containing metal oxide layer is added on a carbon outer layer of an existing core-shell catalyst by utilizing an equivalent-volume impregnation method and a hydrogenation reduction reaction, so that small molecules are effectively inhibited from entering, the electron transmission capability of the core-shell catalyst is improved, and the reaction activity is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst preparation, and specifically relates to a core-shell structure catalyst and a preparation method and application thereof. Background Art

[0002] Core-shell catalysts are composite catalysts composed of a core layer and a shell layer, usually in micron or nanometer size, and are made by combining multiple materials with different boundary structures in an orderly manner through chemical bonds or other forces. At present, core-shell catalysts are considered to be new materials that can simultaneously achieve functional complementarity and morphological optimization of different particles, provide interface effects and shielding effects, and have significant activity and stability. Therefore, they have received great attention in various fields such as electrochemistry, advanced oxidation, batteries, biomedicine, thermal catalysis, and photocatalysis. The core-shell structure is effective in separating two-step reactions and promoting continuous reactions. The shell layer is a protective layer that prevents the penetration of specific molecules from affecting the catalytic efficiency. Therefore, core-shell catalysts have been widely used in this field.

[0003] However, the thickness of the shell directly affects electron transport. If the shell is too thick, the electron transport path becomes longer, hindering electron transport; if it is too thin, it may not be able to effectively protect the material. Therefore, in order to improve the electron transport capacity, it is necessary to precisely control the thickness of the shell, use highly conductive materials such as graphene, carbon nanotubes, and various metal materials as shells, or introduce heterogeneous elements into the shell for doping. Although the core-shell catalysts prepared in this way have excellent catalytic properties in some aspects, this method cannot inhibit the entry of small molecules; at the same time, the traditional core-shell catalysts have weak electron transport capabilities due to the thickness of the carbon outer layer, which greatly affects the reaction process. Summary of the invention

[0004] In view of the above problems, the present invention proposes a multi-layer core-shell structure catalyst and its preparation method and application. By adding a metal oxide layer containing metal on the carbon outer layer of the existing core-shell catalyst, the entry of small molecules is effectively inhibited and the electron transmission ability of the core-shell catalyst is improved, thereby improving the reaction activity.

[0005] In a first aspect, the present invention provides a multilayer core-shell structure catalyst comprising a supported metal catalyst, which comprises a carrier and an active metal bound to the carrier;

[0006] The outer layer of the supported metal catalyst is wrapped with a carbon material layer, and the outer layer of the carbon material is wrapped with a metal oxide layer.

[0007] Preferably, the carrier is one of molecular sieve, carbon material, metal oxide, MOF, COF. It is further preferred that the molecular sieve as the carrier is one of type A, type X, type Y, and type ZSM; the MOF material as the carrier is one of ZIF-8, ZIF-67, MIL-101, HKUST-1, MOF-5, UiO-66, NU-1000, and PCN-22; the COF as the carrier is one of TpPa-1, TP-COF, COF-1, and COF-5; the metal oxide as the carrier is Al 2 O 3 、SiO 2 、TiO 2 、ZrO 2 、CeO 2 , FeOx, TiO 2 ,La 2 O 3 、V 2 O 5 A composite of one or more of any metal oxides.

[0008] Preferably, the carbon material is one of activated carbon, carbon nanotubes, carbon nanofibers and graphene.

[0009] Preferably, the active metal is one of Pd, Pt, Rh, Ir, Fe, Co, Ni, Cu, Zn, Au, Ag, Sn, Mn, and Mo.

[0010] Preferably, in the supported metal catalyst, the mass of the active metal is 1 wt%-5 wt% of the mass of the carrier.

[0011] In a second aspect, the present invention provides a method for preparing the multilayer core-shell structure catalyst comprising a supported metal catalyst as described in the first aspect, comprising the following steps:

[0012] A1. First, the supported metal catalyst is calcined in an atmosphere containing a calcined carbon source at 250-800 ℃ by chemical vapor deposition for 1-8 hours to prepare a carbon-encapsulated catalyst;

[0013] A2. Prepare a metal precursor solution with a metal concentration of 0.1%-20% of the mass of the catalyst to be prepared, and stir for 0-4 hours with ultrasonic assistance to achieve a uniform configuration;

[0014] A3. The prepared metal precursor solution is slowly added dropwise to the carbon-encapsulated catalyst prepared in step A1 by an equal volume impregnation method; after impregnation for 0.5-12 hours, the prepared catalyst is dried in a forced air drying oven at 60-120°C for 4-10 hours;

[0015] A4. The dried catalyst was calcined in a tube furnace at 200-1200°C for 2-6 hours under an inert atmosphere, and then switched to H 2 / Ar mixed gas is reduced at 100-600°C for 1-6h; after natural cooling, it is ground to obtain a finished product.

[0016] Preferably, the calcined carbon source used in step A1 is one of acetylene, ethylene, ethane, glucose, sucrose, polyacrylonitrile, phenolic resin, polyvinyl alcohol, and polystyrene. The calcination temperature of A1 is 400-600° C., and the calcination time is 2-3 h.

[0017] Preferably, in step A3, the catalyst is impregnated with an equal volume of water for 1-6 hours, the drying temperature is 80-110° C., and the drying time is 6-8 hours.

[0018] Preferably, the inert gas used in the inert atmosphere of step A4 is N 2 , Ar, He, the reduction temperature is 300-500℃, and the calcination time is 2-3h.

[0019] In a third aspect, the present invention provides an application of a multilayer core-shell structure catalyst as described in the first aspect in a catalytic hydrogenation reaction of an organic compound, wherein the organic reactant has at least one of the following characteristics: its structural formula contains sulfur, or contains sulfur impurities.

[0020] More specifically, the sulfur-containing organic compound in the structural formula itself can be a sulfur-containing olefin compound or a sulfur-containing aromatic nitro compound, and the sulfur-containing olefin compound can be a biotin precursor (I), 2-[β-(2-thienyl) vinyl] benzoic acid, etc.; the sulfur-containing aromatic nitro compound can be 4-nitroanisole, 2-nitrodiphenyl sulfide, 1-nitrodibenzothiophene, 2-nitro-4-(propylthio)aniline, 4-nitrobenzene mercaptan, 3,3'-sulfonyl dinitrobenzene, etc. The organic compound can also be an organic compound that does not contain sulfur in the structural formula itself, such as a styrene compound or a nitrobenzene compound, which contains sulfur impurities when used as a reactant in the catalytic hydrogenation reaction of the present invention. The sulfur impurities can be organic sulfur compounds, and the organic sulfide can be at least one of thiophene, dibenzothiophene, n-dodecyl mercaptan, ethyl sulfide, diethyl disulfide, etc. The present invention preferably uses the sulfur-containing compound 4-nitroanisole as a probe reaction.

[0021]

[0022] Preferably, the steps of applying include:

[0023] B1. adding an organic compound, a powder of a multilayer core-shell catalyst and a related solvent into a reactor;

[0024] B2. Conduct continuous hydrogenation reaction at a reaction temperature of 80-200° C., a reaction pressure of 0.5-4 MPa and a hydrogen atmosphere to generate a hydrogenation product.

[0025] As further preferred, the relevant solvent is one or more of methanol, ethanol, toluene, dioxane, N,N-dimethylformamide, and tetrahydrofuran.

[0026] As a further preference, in step B2, the reaction temperature is 120-150° C. and the reaction pressure is 3 MPa.

[0027] The beneficial effects produced by the present invention are:

[0028] 1. The multilayer graphene structure of the multilayer core-shell structure catalyst can effectively prevent the sulfur element in the reaction system from contacting with the internal active metal to produce side reactions, thereby making the catalyst have high stability and target product selectivity.

[0029] 2. The multilayer core-shell structure catalyst has a metal layer wrapped outside the carbon layer, which has excellent electron transport performance, making up for the defect of low activity behind the shell layer of traditional core-shell catalysts.

[0030] 3. The range of materials is wide. The preparation method of the present invention can be used to prepare multilayer core-shell structure catalysts using a variety of supported metal catalysts, carbon sources and metal precursor solutions.

[0031] 4. The present invention uses a multilayer core-shell structure catalyst for the catalytic hydrogenation of 4-nitroanisole. The presence of the carbon material layer and the metal oxide layer significantly improves the stability and reaction activity of the catalyst, showing good anti-sulfur activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a transmission electron microscope image of a multilayer core-shell structure catalyst of the present invention.

[0033] Figure 2 The XRD diagram of a 3wt% Pd / ZSM-5@C-450@5% FeOx-400 catalyst prepared by a method for preparing a multi-layer core-shell structure catalyst of the present invention.

[0034] Figure 3 The present invention discloses an electrochemical impedance spectrum of a 3wt% Pd / ZSM-5@C-450@5% FeOx-400 catalyst prepared by a method for preparing a multi-layer core-shell structure catalyst of the present invention.

[0035] Figure 4 This is a diagram showing the experimental results of applying a multi-layer core-shell structure catalyst of the present invention to a traditional core-shell structure catalyst. DETAILED DESCRIPTION

[0036] The present invention is further described below in conjunction with specific embodiments, but the scope of protection of the present invention is not limited to the described scope.

[0037] Embodiment 1

[0038] 1. Preparation of multilayer core-shell catalyst 3wt% Pd / ZSM-5@C-450@5% FeOx-400

[0039] 3 wt% Pd(OH) was prepared in advance 2 / ZSM-5 catalyst for standby use (load = m Pd / (m Pd +m ZSM-5 )×100%), 1.2 mL H 2 PdCl 4 The solution was immersed in 80 mL of deionized water containing 1.94 g of ZSM-5 support, stirred at 500 r / min at 60 ° C for 4 h, and then the solution pH was adjusted to about 10 with 1 mol / L NaOH aqueous solution. After aging for 2 h, the solution was filtered and dried in a 110 ° C forced air drying oven, and finally ground to 200 mesh to obtain 3 wt% Pd(OH) 2 / ZSM-5 catalyst.

[0040] The prepared catalyst was transferred into a tube furnace and heated under N 2 The temperature was heated to 450 °C at a rate of 5 °C / min under the atmosphere, and then the calcination was continued at this temperature for 2 h, and then the temperature was switched to N 2 The temperature was lowered to room temperature at 2°C / min to obtain a 3wt% Pd / ZSM-5@C-450 catalyst. A 5wt% ferric nitrate solution was prepared as a precursor solution, and an equal volume of the solution was impregnated onto the catalyst obtained above. After impregnation for 6 hours, the catalyst was transferred to a 110°C forced air drying oven and dried for 8 hours. The catalyst was then ground thoroughly and dried again in a tube furnace at N 2 After heating to 400 °C at a rate of 5 °C / min for 2 h, the atmosphere was switched to 5% H 2 / Ar mixed gas reduction for 2h, and then ground again after natural cooling to finally obtain a multilayer core-shell structure catalyst 3wt%Pd / ZSM-5@C-450@5%FeOx-400.

[0041] Figure 1 The TEM image of the catalyst prepared in the example shows the microscopic particle image of the multi-layer core-shell structure catalyst, the inner layer component is Pd nanoparticles, the middle layer component is graphene, and the outer layer component is FeOx. Figure 2This is the XRD diagram of the catalyst 3wt% Pd / ZSM-5@C-450@5% FeOx-400 prepared in this example. In this figure, compared with the catalyst not wrapped with a metal oxide layer, 3wt% Pd / ZSM-5@C-450@5% FeOx-400 does not show a diffraction peak of Pd, but there is a small amount of diffraction peak of Fe, indicating that FeOx is exposed in the outer layer of the catalyst and Pd is wrapped in the graphene shell. Figure 3 Schematic diagram comparing the electron transmission capacity of Example 1 and traditional core-shell catalysts, wherein the traditional core-shell catalyst has a larger arc radius in the high-frequency region, indicating that the electron transmission capacity is poor. On the contrary, the electron transmission capacity of the multilayer core-shell catalyst in the present invention is greatly improved.

[0042] 2. The prepared catalyst 3wt% Pd / ZSM-5@C-450@5% FeOx-400 was applied to the selective catalytic hydrogenation of 4-nitroanisole to resist sulfur:

[0043] Take 10g 4-nitroanisole and 80mL toluene in a 250mL reactor, add 0.3g 3wt% Pd / ZSM-5@C-450@5% FeOx-400 catalyst. After sealing the reactor, use N 2 Repeatedly replace the air in the reactor to check the air tightness of the reactor. The reaction was carried out at 130°C and the mechanical stirring rate was controlled at 1000 r·min -1 , H 2 The pressure was controlled at 3MPa. After the reaction lasted for 1 hour, the mixture was cooled naturally, filtered, and dried in a 110°C forced air drying oven for 6 hours before next use. The hydrogenation product was quantitatively analyzed by an Angilent 7890B gas chromatograph. After 1 hour of reaction, the conversion rate of the raw material was determined to be 99.9%, and the selectivity of the target product was 99.6%.

[0044] Embodiment 2 to Embodiment 7

[0045] 1. Preparation of multilayer core-shell catalyst wt% Pd / ZSM-5@C-450@5% MOx-400

[0046] Preparation of 3wt% Pd(OH) 2 / ZSM-5 catalyst for standby use (load = m Pd / (m Pd +m ZSM-5 )×100%), specifically, 1.2 mL H 2 PdCl 4The solution was immersed in 80 mL of deionized water containing 1.94 g of ZSM-5 support, stirred at 500 r / min at 60 ° C for 4 h, and then the solution pH was adjusted to about 10 with 1 mol / L NaOH aqueous solution. After aging for 2 h, the solution was filtered and dried in a 110 ° C forced air drying oven, and finally ground to 200 mesh to obtain 3 wt% Pd(OH) 2 / ZSM-5 catalyst.

[0047] The prepared catalyst was transferred into a tube furnace and heated under N 2 The temperature was heated to 450 °C at a rate of 5 °C / min under the atmosphere, and then the calcination was continued at this temperature for 2 h, and then the temperature was switched to N 2 The catalyst was cooled to room temperature at a rate of 2°C / min to obtain a 3wt% Pd / ZSM-5@C-450 catalyst. A 5wt% nitrate solution of Co, Ni, Cu, Zn, Ag or Pt was prepared as a precursor solution, and an equal volume of the solution was impregnated onto the catalyst obtained above. After impregnation for 6 hours, the catalyst was transferred to a 110°C forced air drying oven and dried for 8 hours. The catalyst was then ground thoroughly and heated to 400°C in a tube furnace at a rate of 5°C / min and heated to 400°C at N 2 After calcination at 400 °C for 2 h, the atmosphere was switched to 5% H 2 / Ar mixed gas reduction for 2h, and then ground again after natural cooling to finally obtain a catalyst 3wt%Pd / ZSM-5@C-450@5%MOx-400 with a multilayer core-shell structure.

[0048] 2. Application of multilayer core-shell structure catalyst wt% Pd / ZSM-5@C-450@5% MOx-400 in the selective catalytic hydrogenation of 4-nitroanisole to resist sulfur:

[0049] Take 10g 4-nitroanisole and 80mL toluene in a 250mL reactor, add 0.3g 3wt% Pd / ZSM-5@C-450@5% MOx-400 catalyst. After sealing the reactor, use N 2 Repeatedly replace the air in the reactor to check the air tightness of the reactor. The reaction was carried out at 130°C and the mechanical stirring rate was controlled at 1000 r·min -1 , H 2 The pressure was controlled at 3 MPa. After the reaction lasted for 1 hour, the mixture was cooled naturally, filtered, and dried in a 110°C forced air drying oven for 6 hours before next use. The hydrogenation product was quantitatively analyzed by an Angilent 7890B gas chromatograph. The experimental results are shown in Table 1.

[0050] Table 1 - Evaluation of the performance of 3wt%Pd / ZSM-5@C-450@5%MOx-400 catalyst prepared with outer metal.

[0051]

[0052] Embodiment 8 to Embodiment 11

[0053] 1. Preparation of multilayer core-shell catalyst 3wt% Pd / ZSM-5@C x -450@5%MOx-400

[0054] 3 wt% Pd(OH) was prepared in advance 2 / ZSM-5 catalyst for standby use (load = m Pd / m Pd +m ZSM-5 )×100%), specifically, 1.2 mL H 2 PdCl 4 The solution was immersed in 80 mL of deionized water containing 1.94 g of ZSM-5 support, stirred at 500 r / min at 60 ° C for 4 h, and then the solution pH was adjusted to about 10 with 1 mol / L NaOH aqueous solution. After aging for 2 h, the solution was filtered and dried in a 110 ° C forced air drying oven, and finally ground to 200 mesh to obtain 3 wt% Pd(OH) 2 / ZSM-5 catalyst.

[0055] The prepared catalyst was transferred into a tube furnace and heated under N 2 The temperature was heated to 450 °C at a rate of 5 °C / min under N atmosphere, and then switched to ethylene, ethane, glucose vapor, sucrose vapor, or one of them. The calcination was continued at this temperature for 2 h, and then switched to N 2 The catalyst was cooled to room temperature at a rate of 2°C / min to obtain a 3wt% Pd / ZSM-5@C-450 catalyst. A 5wt% Fe nitrate solution was prepared as a precursor solution, and an equal volume of the solution was impregnated onto the catalyst obtained above. After impregnation for 6 hours, the catalyst was transferred to a 110°C forced air drying oven and dried for 8 hours. The catalyst was then ground thoroughly and heated to 400°C in a tube furnace at a rate of 5°C / min and heated to 400°C at N 2 After calcination at 400 °C for 2 h, the atmosphere was switched to 5% H 2 / Ar mixed gas reduction for 2h, and then ground again after natural cooling. Finally, a multilayer core-shell structure catalyst 3wt% Pd / ZSM-5@C was obtained. x -450@5%FeOx-400.

[0056] 2. Multilayer core-shell catalyst 3wt% Pd / ZSM-5@C x Application of -450@5%FeOx-400 in the selective catalytic hydrogenation of 4-nitrothioanisole to resist sulfur:

[0057] Take 10g 4-nitrothioanisole and 80mL toluene in a 250mL reactor, add 0.3g 3wt% Pd / ZSM-5@C x -450@5%FeOx-400 catalyst. After sealing the kettle, use N 2 Repeatedly replace the air in the reactor to check the air tightness of the reactor. The reaction was carried out at 130°C and the mechanical stirring rate was controlled at 1000 r·min -1 , H 2 The pressure was controlled at 3 MPa. After the reaction lasted for 1 hour, the mixture was cooled naturally, filtered, and dried in a 110°C forced air drying oven for 6 hours before next use. The hydrogenation product was quantitatively analyzed by an Angilent 7890B gas chromatograph. The experimental results are shown in Table 2.

[0058] Table 2 - Evaluation of the performance of metal catalysts coated with different carbon sources.

[0059]

[0060]

[0061] Embodiment 12 to Embodiment 18

[0062] 1. Preparation of multilayer core-shell catalyst 3wt% M / ZSM-5@C-450@5%FeOx-400

[0063] Prepare 3wt% M(OH) in advance 2 / ZSM-5 catalyst for standby use (load = m M / m M +m ZSM-5 )×100%), specifically, one of the nitrate solutions of Pt, Rh, Au, Ag, Fe, Co or Ni as a precursor solution is impregnated into 80 mL of deionized water containing 1.94 g of a ZSM-5 carrier, stirred at 500 r / min at 60°C for 4 h, and then the solution pH is adjusted to about 10 with a 1 mol / L NaOH aqueous solution. After aging for 2 h, the solution is filtered and dried in a 110°C forced air drying oven, and finally ground to 200 mesh to obtain 3 wt% M(OH) 2 / ZSM-5 catalyst. The prepared catalyst was transferred into a tube furnace and heated under N 2 The temperature was heated to 450 °C at a rate of 5 °C / min under the atmosphere, and then the calcination was continued at this temperature for 2 h, and then the temperature was switched to N 2The catalyst was cooled to room temperature at a rate of 2°C / min to obtain a 3wt% M / ZSM-5@C-450 catalyst. A 5wt% Fe-containing precursor solution was prepared and an equal volume of the solution was impregnated onto the catalyst obtained above. After impregnation for 6 hours, the catalyst was transferred to a 110°C forced air drying oven and dried for 8 hours. The catalyst was then ground thoroughly and heated to 400°C in a tube furnace at a rate of 5°C / min and heated under N 2 After calcination at 400°C for 2h under atmosphere, the mixture was switched to 5% H2 / Ar for reduction for 2h, and then ground again after natural cooling. Finally, a multilayer core-shell structure catalyst 3wt% M / ZSM-5@C-450@5%FeOx-400 was obtained.

[0064] 2. Application of multilayer core-shell structure catalyst 3wt% M / ZSM-5@C-450@5% FeOx-400 in the selective catalytic hydrogenation of 4-nitroanisole to resist sulfur:

[0065] Take 10g 4-nitroanisole and 80mL toluene in a 250mL reactor, add 0.3g 3wt% M / ZSM-5@C-450@5%FeOx-400 catalyst. After sealing the reactor, use N 2 Repeatedly replace the air in the reactor to check the air tightness of the reactor. The reaction was carried out at 130°C and the mechanical stirring rate was controlled at 1000 r·min -1 , H 2 The pressure was controlled at 3 MPa, and the reaction lasted for 1 hour, then the mixture was cooled naturally, filtered, and dried in a 110°C forced air drying oven for 6 hours before next use. The hydrogenation product was quantitatively analyzed by an Angilent 7890B gas chromatograph. The experimental results are shown in Table 3.

[0066] Table 3 - Evaluation of the performance of 3wt% M / ZSM-5@C-450@5% MOx-400 catalyst prepared with inner metal.

[0067]

[0068]

[0069] Embodiment 19 to Embodiment 20

[0070] 1. Preparation of multilayer core-shell catalyst 3wt% Pd / ZSM-5@C-450@x%FeOx-400

[0071] 3 wt% Pd(OH) was prepared in advance 2 / ZSM-5 catalyst for standby use (load = m Pd / m Pd +m ZSM-5 ×100%), specifically, 1.2 mL of H2 PdCl 4 The solution was immersed in 80 mL of deionized water containing 1.94 g of ZSM-5 carrier, stirred at 500 r / min at 60 ° C for 4 h, and then the pH of the solution was adjusted to about 10 with 1 mol / L NaOH aqueous solution. After aging for 2 h, the solution was filtered and dried in a 110 ° C forced air drying oven, and finally ground to 200 mesh to obtain 3 wt% Pd(OH) 2 / ZSM-5 catalyst.

[0072] The prepared catalyst was transferred into a tube furnace and heated under N 2 The temperature was heated to 450 °C at a rate of 5 °C / min under the atmosphere, and then the calcination was continued at this temperature for 2 h, and then the temperature was switched to N 2 The catalyst was cooled to room temperature at a rate of 2°C / min to obtain a 3wt% Pd / ZSM-5@C-450 catalyst. Precursor solutions containing Fe at different contents were prepared and impregnated onto the catalyst obtained above in equal volumes. After impregnation for 6 hours, the catalyst was transferred to a 110°C forced air drying oven and dried for 8 hours. The catalyst was then ground thoroughly and heated to 400°C in a tube furnace at a rate of 5°C / min and heated under N 2 After calcination at 400 °C for 2 h, the atmosphere was switched to 5% H 2 / Ar mixed gas reduction for 2h, and then ground again after natural cooling to finally obtain a multilayer core-shell structure catalyst 3wt%Pd / ZSM-5@C-450@x%FeOx-400.

[0073] 2. Application of multilayer core-shell structure catalyst 3wt% Pd / ZSM-5@C-450@x%FeOx-400 in the selective catalytic hydrogenation of 4-nitroanisole to resist sulfur:

[0074] Take 10g 4-nitroanisole and 80mL toluene in a 250mL reactor, add 0.3g 3wt% Pd / ZSM-5@C-450@x%FeOx-400 catalyst. After sealing the reactor, use N 2 Repeatedly replace the air in the reactor to check the air tightness of the reactor. The reaction was carried out at 130°C and the mechanical stirring rate was controlled at 1000 r·min -1 , H 2 The pressure was controlled at 3MPa. After the reaction lasted for 1 hour, the mixture was cooled naturally, filtered, and dried in a 110°C forced air drying oven for 6 hours before next use. The hydrogenation product was quantitatively analyzed by an Angilent 7890B gas chromatograph. After 1 hour of reaction, the conversion rate of the raw material was determined to be 99.9%, and the selectivity of the target product was 99.6%.

[0075] Table 4 - Effect of different Fe contents on catalyst performance

[0076]

[0077] Embodiment 23 to Embodiment 26

[0078] Take 10g 4-nitroanisole and 80mL toluene in a 250mL reactor, add 0.3g 3wt% Pd / ZSM-5@C-450@5% FeOx-400 catalyst. After sealing the reactor, use N 2 Repeatedly replace the air in the reactor to check the air tightness of the reactor. The reaction was carried out at different reaction temperatures, and the mechanical stirring rate was controlled at 1000r·min -1 , H 2 The pressure was controlled at 3 MPa, and the reaction lasted for 1 hour, then the mixture was cooled naturally, filtered, and dried in a forced air drying oven at 110°C for 6 hours before next use. The hydrogenation product was quantitatively analyzed by an Angilent 7890B gas chromatograph.

[0079] Table 4-3 Evaluation of the performance of wt% Pd / ZSM-5@C-450@5% FeOx-400 catalyst at different temperatures.

[0080]

[0081]

[0082] Embodiment 27

[0083] In order to demonstrate the high conversion rate and high stability of the metal oxide layer of 3wt% Pd / ZSM-5@C-450@5% FeOx-400 in the hydrogenation reaction of sulfur-containing unsaturated compounds, two control groups were set up:

[0084] Comparative Example 1: 10 g of 4-nitrothioanisole and 80 mL of toluene were placed in a 250 mL reactor, and 0.3 g of 3 wt% Pd / ZSM-5@C-450 catalyst was added. 2 Repeatedly replace the air in the reactor to check the air tightness of the reactor. The reaction was carried out at 130°C and the mechanical stirring rate was controlled at 1000 r·min -1 , H 2 The pressure was controlled at 3 MPa, and the reaction lasted for 1 hour, then the mixture was cooled naturally, filtered, and dried in a forced air drying oven at 110°C for 6 hours before next use. The hydrogenation product was quantitatively analyzed by an Angilent 7890B gas chromatograph.

[0085] Comparative Example 2: ZSM-5 was placed in a tube furnace at N 2 The temperature was heated to 450 °C at a rate of 5 °C / min under the atmosphere, and then the calcination was continued at this temperature for 2 h, and then the temperature was switched to N 2The temperature was lowered to room temperature at 2°C / min to obtain ZSM-5@C-450 catalyst. A 5wt% Fe-containing precursor solution was prepared and an equal volume of the solution was impregnated onto the catalyst obtained above. After impregnation for 6 hours, the catalyst was transferred to a 110°C forced air drying oven and dried for 8 hours. The catalyst was then ground thoroughly and heated to 400°C in a tube furnace at a rate of 5°C / min under N 2 After calcination at 400°C for 2 hours under atmosphere, the mixture was switched to 5% H2 / Ar for reduction for 2 hours, and then ground again after natural cooling. Finally, the catalyst ZSM-5@C-450@5%FeOx-400 was obtained.

[0086] Take 10g 4-nitroanisole and 80mL toluene in a 250mL reactor, add 0.3g ZSM-5@C-450@5%FeOx-400 catalyst. After sealing the reactor, use N 2 Repeatedly replace the air in the reactor to check the air tightness of the reactor. The reaction was carried out at 130°C and the mechanical stirring rate was controlled at 1000 r·min -1 , H 2 The pressure was controlled at 3 MPa, and the reaction lasted for 1 hour, then the mixture was cooled naturally, filtered, and dried in a forced air drying oven at 110°C for 6 hours before next use. The hydrogenation product was quantitatively analyzed by an Angilent 7890B gas chromatograph.

[0087] Table 5 - Performance evaluation of different catalysts.

[0088]

[0089] Subsequently, the catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 were used 15 times under the same conditions to obtain the conversion rate and reaction time as shown in the following table: Figure 4 As shown. The conversion rate of the multilayer core-shell structure catalyst of Example 1 is close to 99.9% in 15 repeated uses, the conversion rate of the conventional core-shell structure catalyst of Comparative Example 1 is 37.2% in the first four uses, and the conversion rate of the core-shell structure catalyst lacking active metal of Comparative Example 2 is 0%, which is sufficient to prove that the metal oxide layer of the multilayer core-shell structure catalyst of the present invention plays an important role in improving stability and reaction activity.

[0090] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A multilayer core-shell structure catalyst, characterized in that: The supported metal catalyst comprises a carrier and an active metal combined with the carrier; the outer layer of the carrier is wrapped with a carbon material layer, and the outer layer of the carbon material layer is wrapped with a metal oxide layer.

2. A multilayer core-shell structure catalyst according to claim 1, characterized in that: The active metal is one of Pd, Pt, Rh, Ir, Fe, Co, Ni, Cu, Zn, Au, Ag, Sn, Mn, and Mo, and the mass of the active metal is 0.1wt%-15% of the total mass of the supported metal catalyst.

3. A multilayer core-shell structure catalyst according to claim 1, characterized in that: The carrier is one of molecular sieve, carbon material, metal oxide, MOF, COF; the molecular sieve used as the carrier is one of type A, type X, type Y, and type ZSM; the MOF material used as the carrier is one of ZIF-8, ZIF-67, MIL-101, HKUST-1, MOF-5, UiO-66, NU-1000, and PCN-22; the COF used as the carrier is one of TpPa-1, TP-COF, COF-1, and COF-5; the metal oxide used as the carrier is one of Al2O3, SiO2, TiO2, ZrO2, CeO2, FeOx, TiO2, La2O3, and V2O5, or a combination of any multiple of the above metal oxides.

4. The method for preparing a multilayer core-shell structure catalyst according to claim 1, comprising the steps of: A1. First, the supported metal catalyst is calcined in an atmosphere containing a calcined carbon source at 250-800 ℃ by chemical vapor deposition for 1-8 hours to prepare a carbon-encapsulated catalyst; A2. Prepare a metal precursor solution with a metal concentration of 0.1%-20% of the mass of the catalyst to be prepared, and stir for 0-4 hours with ultrasonic assistance to achieve a uniform configuration; A3. The prepared metal precursor solution is slowly added dropwise to the carbon-encapsulated catalyst prepared in step A1 by an equal volume impregnation method; after impregnation for 0.5-12 hours, the prepared catalyst is dried in a forced air drying oven at 60-120°C for 4-10 hours; A4. The dried catalyst is calcined at 200-1200°C in an inert atmosphere in a tubular furnace for 2-6 hours, and then switched to 5% H2 / Ar mixed gas for reduction at 100-600°C for 1-6 hours; after natural cooling, it is ground to obtain the finished product.

5. The method for preparing a multilayer core-shell structure catalyst according to claim 4, characterized in that: The calcined carbon source used in step A1 is one of acetylene, ethylene, ethane, glucose, sucrose, polyacrylonitrile, phenolic resin, polyvinyl alcohol, and polystyrene. The calcination temperature of A1 is 400-600° C. and the calcination time is 2-3 hours.

6. The method for preparing a multilayer core-shell structure catalyst according to claim 4, characterized in that: The metal precursor solution in step A2 is a nitrate or chloride solution of Pd, Pt, Rh, Ir, Fe, Co, Ni, Cu, Zn, Au, Ag, Sn, Mn, or Mo.

7. The method for preparing a multilayer core-shell structure catalyst according to claim 4, characterized in that: In step A3, the equal volume impregnation time of the catalyst is 1-6h, the drying temperature is 80-110°C, and the drying time is 6-8h; the inert gas used in the inert atmosphere of step A4 is one of N2, Ar, and He, the reduction temperature is 300-500°C, and the calcination time is 2-3h.

8. The use of a multi-layer core-shell structure catalyst according to claim 1 in catalytic hydrogenation of sulfur-containing compounds to resist sulfur, the steps comprising: B1. The unsaturated compound containing sulfur impurities, the core-shell catalyst powder and the related solvent are added to the reactor; B2. Conduct continuous hydrogenation reaction at a reaction temperature of 80-200° C., a reaction pressure of 0.5-4 MPa and a hydrogen atmosphere to generate a hydrogenation product.

9. Use of a core-shell structure catalyst according to claim 8 in catalytic hydrogenation and sulfur resistance of sulfur-containing compounds, characterized in that: The relevant solvent is one or more of methanol, ethanol, toluene, dioxane, N,N-dimethylformamide, and tetrahydrofuran; and the unsaturated compound is an olefin sulfur-containing compound or an aromatic nitro sulfur-containing compound.

10. Use of a core-shell structure catalyst according to claim 8 in catalytic hydrogenation and sulfur resistance of sulfur-containing compounds, characterized in that: In step B2, the reaction temperature is 120-150°C and the reaction pressure is 3 MPa.

Citation Information

Patent Citations

  • Compound catalyst with nanometer core-shell structure and preparing method of compound catalyst

    CN107890863A

  • Double-shell core-shell structure metal catalyst and preparation method thereof

    CN111036198A

  • Interlayer platinum-cobalt bimetallic catalyst, preparation method thereof and application of interlayer platinum-cobalt bimetallic catalyst in catalytic directional synthesis of secondary amine

    CN115318328A

  • Transition metal catalyst as well as preparation method and application thereof

    CN117899873A

  • Metal-Carbon Composite Supported Catalyst for Hydrogen Production Using Co-Evaporation and Method of Preparing the Same

    US20140087939A1